Synthesis of one-dimensional atomic chain LiMo3Se3 through ion-exchange reaction from InMo3Se3: Kinetics and thermodynamics - Jeon, Jiho; Oh, Seungbae; Choi, Kyung Hwan; Chae, Sudong; Woo, Chaeheon; Dong, Xue; Asghar, Ghulam; Ahn, Jungyoon; Kim, Tae Yeong; Ali, Junaid; Yu, Hak Ki; Choi, Jae Young (Ceramics International, 2021)
For the atomic unit dispersion of Mo3Se3− (a negatively charged atomic chain material that forms bulk crystals through ionic bonds with cations), LiMo3Se3 crystals were synthesized by an ion-exchange reaction from InMo3Se3 (InMo3Se3 + LiI → LiMo3Se3 + InI). The temperature- and time-dependent kinetics of the ion-exchange reaction were studied. The change in the lattice constant, obtained through X-ray diffraction analysis, showed a reaction pattern corresponding to random walk diffusion within the atomic chain. The temperature-specific experiments (Arrhenius plot) confirmed that the ion-exchange activation energy was approximately 0.565 eV. By dispersing the LiMo3Se3 synthesized through an optimized ion-exchange reaction in an aqueous solution, it was confirmed that the one-dimensional (1D) nanostructure was well dispersed. Based on the results of this experiment, it is expected that it will be possible to lay the foundation for the application of water-dispersible one-dimensional materials to various bio fields.
Keywords: Atomic chains; Atomic units; Bulk crystals; Ion exchange reactions; Ionic bonds; Kinetics and thermodynamics; Negatively charged; One-dimensional atomic chains; One-dimensional materials; Synthesised; Atomic chain; Ion-exchange; LiMo3Se3; One-dimensional materials